2013
DOI: 10.3390/ijerph10127193
|View full text |Cite
|
Sign up to set email alerts
|

Characterising the Smoking Status and Quit Smoking Behaviour of Aboriginal Health Workers in South Australia

Abstract: The study objectives were to characterise the smoking status and quit smoking behaviour of Aboriginal Health Workers (AHWs) in South Australia (SA), Australia; and identify the psychosocial, socio-demographic, and household smoking characteristics that distinguish smokers from quitters and never smokers. A self-reported cross-sectional survey was completed by AHWs in SA. Non-parametric statistics were used for inferential analyses. Eighty-five AHWs completed surveys representing a response rate of 63.0%. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
1
7
1
Order By: Relevance
“…Our national estimate of staff smoking prevalence was at the lower end of previous smaller local and regional studies, and much lower than the largest previous study (51%, n = 85), which also reported the highest (but still a modest) response rate of 63% 3 , 12 . However, these studies concentrated on AHWs (variously defined) rather than all Aboriginal and Torres Strait Islander staff.…”
Section: Discussioncontrasting
confidence: 69%
“…Our national estimate of staff smoking prevalence was at the lower end of previous smaller local and regional studies, and much lower than the largest previous study (51%, n = 85), which also reported the highest (but still a modest) response rate of 63% 3 , 12 . However, these studies concentrated on AHWs (variously defined) rather than all Aboriginal and Torres Strait Islander staff.…”
Section: Discussioncontrasting
confidence: 69%
“…Although recognition and treatment of mental health disorders have made marked progress in Saudi Arabia (27), some Saudis release stress and anxiety through tobacco use (18). Our study confirmed that psychological problems such as depression play a significant role in changes in smoking behaviour, which is consistent with findings from western and East Asian countries (28)(29)(30)(31). In contrast to the above findings, in the present study, Saudi male university students smoked to improve their psychological wellbeing, such as gaining pride or confidence, while not having any indications of psychological distress.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, health prioritisation and knowledge of health effects were protective against substance use. Enjoying smoking was identified as a risk factor for continued smoking ( Johnston and Thomas, 2008 , Maksimovic et al, 2013 , Gamarania et al, 1998 ), but prioritising health was consistently reported to protect against tobacco and cannabis use ( Brown et al, 2016 , Thomas et al, 2008 , Bond et al, 2012 , Maksimovic et al, 2013 , Jacups and Rogerson, 2015 , Wood et al, 2008 ). Qualitative studies reported that health prioritisation occurred after a personal health crisis, which led to a positive life transition encouraging substance cessation ( Bond et al, 2012 , Wood et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative studies reported that health prioritisation occurred after a personal health crisis, which led to a positive life transition encouraging substance cessation ( Bond et al, 2012 , Wood et al, 2008 ). Pregnancy was similarly found to motivate substance cessation ( Gould et al, 2017 , Maksimovic et al, 2013 ). One qualitative study found individuals were more likely to abstain or cease tobacco use if they gained knowledge of the adverse health effects of smoking ( Gamarania et al, 1998 ).…”
Section: Resultsmentioning
confidence: 99%